OS 06-02 MULTIPLE ANTIHYPERTENSIVE MEDICATION USE, RESISTANT HYPERTENSION AND OUTCOMES IN THE UNITED STATES: FINDINGS FROM NHANES 1988 TO 2012. (September 2016) - Liu, Longjian; Dow, Jessica; Simon, Barbara; Eisen, Howard
Abstract : Objective: Multiple medication use in patients with hypertension (HTN) is a common clinical problem faced by both primary and specialists. Patients who remain to have higher BP in spite of the concurrent use of 3 antihypertensive agents of different classes are defined as resistant hypertension (RH). In the study we aimed to identify the prevalence of RH, and examined its association with mortality from all-cause and cardiovascular disease (CVD). Design and Method: Data from the U.S. National Health and Nutrition Examination Surveys (NHANES) 1988 – 2012 were analyzed cross-sectionally on the burned of RH using logistical regression models, and analyzed prospectively on its association with mortality using Cox regression models. Results: Of 18, 471 patients with HTN (M: 8411, F: 10060), 72.8% in males and 75.9% in females took antihypertensive medications. Whites had the highest prevalence (77.4%), followed by Blacks (74.8%), and Hispanics (67.2%), (p < 0.001). The prevalence of males who took 1, 2 or ≥3 antihypertensive medications were 67.1%, 25.0%, and 8%, and the corresponding values were 68.7%, 25.3%, and 6% in females. Blacks has the highest prevalence of RH (9.4%), followed by Whites (6.1%), and Hispanics (5.8%), (p < 0.001). Patients with RH had significantly higher risk of mortality from all-cause (hazard ratio, HR = 1.82, 95%CI 1.21–3.45, p < 0.001), and CVD (HR: 2.16, 95%CI: 1.72 – 4.65, p < 0.001). Conclusions: The study, using the U.S. nationally representative data, indicates that RH poses a serious clinical and public health problem for all racial and ethnical groups. Further large-scale prospective studies are needed to extend and confirm the current findings.